Solution of Moving Boundary Space-Time Fractional Burger’s Equation - E. A.-B. Abdel-Salam; E. A. Yousif; Y. A. S. Arko; E. A. E. Gumma (Journal of Applied Mathematics)
The fractional Riccati expansion method is used to solve fractional differential equations with variable coefficients. To illustrate the effectiveness of the method, the moving boundary space-time fractional Burger’s equation is studied. The obtained solutions include generalized trigonometric and hyperbolic function solutions. Among these solutions, some are found for the first time. The linear and periodic moving boundaries for the kink solution of the Burger’s equation are presented graphically and discussed.